"Oh take some man-up pills": A life-history study of muscles, masculinity, and the threat of injury. Issue 2 (August 2020) - Cranswick, Ieuan; Richardson, David; Littlewood, Martin; Tod, David
Highlights: Men construct socio-culturally shaped masculine performance narratives. Muscularity is a form of aesthetic and instrumental bodily masculine capital. Realignment narratives guide men's responses to narrative wreckage and disruption. Realignment narratives offer blueprint to maintain and restore normal masculinity. Realignment narratives are influenced by sociocultural interactions and context. Abstract: The current study explored the life-histories of 10 wt training men and aimed to understand the role muscularity played in their masculine identities. Additionally, the study sought to gain insight into the men's responses to experiences (e.g., injury) that threaten their muscular masculinity. Semi-structured interviews and life-history timelines allowed interviewees reflect on their muscular desires, their injury responses, and the influential experiences, people, and events that shaped their perceptions and identities. The current findings demonstrated how men's muscular desires were part of a socially shaped overarching masculine performance narrative, whereby muscularity played a central role as a form of aesthetic and instrumental bodily capital. The overarching narrative were blueprints for the men's identities, and at times of threat the men constructed different realignment narratives to help maintain and restore their masculine identities and performances. The current study demonstrated the influence social observations and interactions over the life course had on narrative and identity construction and the meanings attributed to muscularity. The findings inform research of the need to embrace multiple masculine narratives to understand the potentially diverse meanings muscularity holds for men in different social contexts.